Improvement of energy efficiency and effectiveness of cooking in solar electric slow cooker for tropical countries - Hasan, Rayed Md. Muhaymin; Islam, Nahian; Khan, Mehrab Azam (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.